الجوائح والأمراض أواخر العهد العثماني 1700-1830م - سلاف بن جعفر (جامعة محمد بوضياف بالمسيلة, 2025)
شهدت إيالة الجزائر خلال الفترة الممتدة من 1700 إلى 1830 سلسلة من الجوائح والكوارث الطبيعية التي كان لها أثر بالغ على المجتمع والبيئة. فقد عرفت هذه المرحلة انتشار أمراض معدية وأوبئة فتاكة مثل الطاعون، الكوليرا، الجدري، والتيفوس، إلى جانب كوارث طبيعية كالمجاعات، الجفاف، الزلازل، والفيضانات، فضلاً عن اجتياح أسراب الجراد. لم تكن هذه الظواهر مجرد حوادث عابرة، بل شكلت تحديات بنيوية كشفت هشاشة المنظومات الصحية والاجتماعية آنذاك. وتهدف هذه الدراسة إلى تحليل جذور هذه الجوائح، والتعرف على تداعياتها على البنية الديمغرافية والاقتصادية، بالإضافة إلى سبل تعامل السلطات والسكان معها، كما تبرز أهمية التفاعل بين الإنسان وبيئته في ظل هذه الأزمات، لتقدم في النهاية قراءة تاريخية علمية تعزز فهمنا لطبيعة الأوبئة وآليات انتشارها في سياقات مشابهة. Between 1700 and 1830, the Regency of Algiers experienced a series of pandemics and natural disasters that had a profound impact on both society and the environment. This period was marked by the spread of deadly infectious diseases such as plague, cholera, smallpox, and typhus, in addition to natural catastrophes like famines, droughts, earthquakes, floods, and locust invasions. These events were not merely isolated incidents but represented structural challenges that revealed the fragility of the health and social systems of the time. This study aims to analyze the underlying causes of these outbreaks and explore their effects on the demographic and economic fabric, as well as the ways in which authorities and populations responded. It also highlights the importance of the interaction between humans and their environment during times of crisis, ultimately offering a scientific and historical perspective that enhances our understanding of the nature and spread of epidemics in similar contexts.